Correction: Muddy boots beget wisdom: Implications for rare or endangered plant species distribution models (Diversity, (2019) 11, 1, 10.3390/d11010010) - Oleas, Nora (2020)
1. Error in Figure An error on our paper [1] came to our attention. The reason for the correction is a mistake in Figure 1. The names of the species were switched between P. schizantha and P. dubia. The correct new Figure 1 is shown below: The above error did not change the results and conclusions of our paper. However, the authors would like to apologize for any inconvenience caused to the readers by this error. (Figure Presented). Conflicts of Interest: The authors declare no conflict of interest.